Handbook of research on deception, fake news, and misinformation online - Chiluwa, Innocent; Samoilenko, Sergei A., 1976- (Advances in media, entertainment, and the arts (AMEA) book series., 2019)
"This book examines the various aspects of deceptive behavior and deceptive communication on social media. It also explores fake news and misinformation, character assassination and libel, online financial scams, romance scams, business deceits and commercial lies, political deceptions, and religious lies"--